Does Fear of the New Coronavirus Lead to Low-Carbon Behaviors: The Moderating Effect of Outcome Framing - Liu W; Shao W; Wang Q (Dove Medical Press, 2021)
Wenlong Liu,1,2 Wen Shao,3 Qunwei Wang2 1School of Management, Fudan University, Shanghai, People's Republic of China; 2College of Economics and Management, Nanjing University of Aeronautics and Astronautics, Nanjing, Jiangsu, People's Republic of China; 3School of Economics & Management, Southeast University, Nanjing, Jiangsu, People's Republic of ChinaCorrespondence: Wenlong Liu Email willenliu@nuaa.edu.cnPurpose: Air pollution has been found to aggravate the infection and mortality of COVID-19, leading to increasing attention on pro-environmental behaviors. Considering individuals' psychological distance from COVID-19, this research aims to examine the relationship between fear of COVID-19, air pollution concern, and low-carbon behaviors.Methods: Two survey-based studies were conducted in this research. Study 1 consisted of 323 participants and examined the relationships between psychological distance (PD) from COVID-19, fear of COVID-19, air pollution concern, and low-carbon behaviors. Study 2 identified the moderating effect of outcome framing using an intergroup experiment in which 304 participants were randomly assigned to two groups (gain framing vs loss framing).Results: The results of Study 1 showed that the closer the PD was, the higher the fear was. Fear of COVID-19 and low-carbon behaviors were positively associated. Additionally, air pollution concern acted as a mediator in their relationship. The results of the moderating effect test in Study 2 showed that fear and air pollution concern led to higher low-carbon behavioral intention within gain framing than within loss framing.Conclusion: This research revealed that personal fear of public health emergencies will lead to environmental pollution concern and pro-environmental behaviors, and information from the outside plays a moderating role. The results provide implications for policy advocacy of the health and environmental sectors and for guiding people's low-carbon behaviors.Keywords: COVID-19, psychological distance, fear, air pollution concern, low-carbon behavior, outcome framing